Single-cell multi-omics analysis reveals cellular subpopulations associated with relapse in high-risk B-ALL following intensified chemotherapy - Liu, Li; Mao, Xiaoyan; Yang, Chunhui; Li, Na; Zhou, Yan; Zhang, Li; Jiang, Nanjing; Huang, Yu; Yin, Shigang; Xie, Huangfan; Tian, Xin (Frontiers in Immunology, 2025)
IntroductionAcute lymphoblastic leukemia (ALL) is the most prevalent malignant tumor in children, with B-cell ALL (B-ALL) accounting for 85% of cases. Despite advancements in chemotherapy and supportive care, a subset of high-risk B-ALL patients still experience relapse post-treatment. The molecular mechanisms underlying the relapses after intensified chemotherapy remain poorly understood.MethodsWe performed an integrated single-cell multi-omics analysis combining single-cell RNA sequencing (scRNA-seq) and single-cell ATAC sequencing (scATAC-seq) on peripheral blood mononuclear cells (PBMCs) from pediatric high-risk B-ALL patients following early intensified chemotherapy, as well as from healthy controls. Bioinformatic pipelines were applied to assess cellular composition, chromatin accessibility, gene ontology enrichment, spectral clustering, and copy number variation.ResultsSignificant differences in cellular composition were observed between the remission and non-remission groups, with the non-remission group exhibiting a notable increase in HSC/MPP and Pro-B cells. Copy number variation (CNV) analysis also revealed that the CNV levels in HSC/MPP and Pro-B cells were higher in the non-remission group compared to other cell types. We subsequently identified a subcluster associated with resistance to intensified therapy within both the HSC/MPP and Pro-B cell groups. The drug-resistant subcluster of HSC/MPP cells was characterized by high expression of TCF4, EBF1, ERG, AL589693.1, and CRIM1, as well as enrichment of the allograft rejection pathway and the Notch signaling pathway. The drug-resistant subcluster of Pro-B cells was characterized by high expression of RPS29, B2M, RPL41, RPS21, NEIL1, AC007384.1, and CRIM1, as well as enrichment of the B cell receptor signaling pathway.DiscussionOur study identified distinct cellular subpopulations associated with treatment failure, provide insights into the molecular mechanisms underlying treatment resistance in B-ALL and may inform the development of targeted therapies for high-risk patients.